Molecular Dynamics Simulation of Hydrated DPPC Monolayers Using Charge Equilibration Force Fields - Lucas, Timothy R. (2011)
We present results of molecular dynamics simulations of a model DPPC-water monolayer using charge equilibration (CHEQ) force fields which explicitly account for electronic polarization in a classical treatment of intermolecular interactions. The surface pressure, determined as the difference between the monolayer and pure water surface tensions at 323 K, is predicted to be 22.92 ± 1.29 dyne/cm, just slightly below the broad range of experimental values reported for this system. The surface tension for the DPPC-water monolayer is predicted to be 42.35 ± 1.16 dyne/cm, in close agreement with the experimentally determined value of 40.9 dyne/cm. This surface tension is also consistent with the value obtained from DPPC monolayer simulations using state-of-the-art nonpolarizable force fields. The current results of simulations predict a monolayer-water potential difference relative to the pure water-air interface of 0.64 ± 0.02 Volts, an improved prediction compared to the fixed-charge CHARMM27 force field, yet still overestimating the experimental range of 0.3 to 0.45 Volts. Since the charge equilibration model is a purely charge-based model for polarization, the current results suggest that explicitly-modeled polarization effects can offer improvements in describing interfacial electrostatics in such systems.